Prevalence and factors associated with sexual and reproductive health services use among reproductive age women with disabilities: a community based cross-sectional study - Bayew Kelkay Rade; Animut Tagele Tamiru; Getie Lake Aynalem; Eden Bishaw Taye; Mamaru Melkie; Alamirew Abera; Endeshaw Admassu Cherkos; Mengstu Melkamu Asaye (BMC, 2023)
Abstract Background According to International Convention on the Right of Person with Disabilities (CRPD), all nations should discern Sexual and Reproductive Health (SRH) as human rights and needs of all people living with disabilities. Women and girls with disabilities are highly vulnerable to SRH disparities including unintended pregnancy, acquiring sexual transmitted infections and unsafe abortion. Little has known about SRH service uptake and influencing factors among reproductive aged women living with disabilities. Methods A community-based cross-sectional study was conducted from January 1-30, 2021, the central Gondar zone selected districts. A total of 535 reproductive-age (18-49 years) women with disabilities had been interviewed through face-to-face using structured questionnaire. Multistage cluster sampling method was applied. A binary logistic regression model was computed to look the relationship between independent variables and uptake of SRH, and p-value < 0.05 was a cut-off point to declare statistical significance. Results A total of 33.27% (178/535) women with disabilities used at least one SRH service in the last twelve months preceding the survey. Those who had three or more children [AOR = 4.85; 95% CI (1.24-9.71)], autonomy to visit health care facilities [AOR = 3.30; 95% CI (1.45-6.92)], lived with sexual partner [AOR = 9.2; 95% CI (2.84-13.60)], subjected to radio/television in daily bases [AOR = 5.9; 95% CI (1.26-13.04)], autonomy to visit friends and relatives [AOR = 3.95; 95% CI (1.28-12.17)], had a discussion with family members about sexual and reproductive health [AOR = 9.36; 95% CI (3.44-17.47)], and engaged in sexual activity after the age of 18 years [AOR = 7.2; 95% CI (2.51-14.45)] were important predictors for service uptake. Conclusions Only one in three reproductive age women with disabilities used at least one SRH service. These findings suggest that accessing information through mainstream media exposure, having full autonomous to visit friends and families, open discussion with family members, live with sexual partner, having optimal family size and starting sexual act at the recommended age improve the uptake of SRH services. Therefore, the stakeholders (both governmental and non-governmental) need to make efforts to increase the uptake of SRH services.